Seropositivity of hepatitis b surface antigen in tertiary care centre: issues & considerations - Surinder Kumar; Pallavi Sayal; Diksha Budhani; Sumit Kumar (International Journal of Medical Research and Review, 2016)
Background: Hepatitis B virus (HBV) infects more than 300 million people worldwide and is common cause of liver disease and liver cancer. HBV, a member of the Hepadnaviridae family, is a small DNA virus with unusual features similar to retroviruses. HBV replicates through an RNA intermediate and can integrate into the host genome. The unique features of the HBV replication cycle confer a distinct ability of the virus to persist in infected cells.Aims & Objective: This study was designed to determine HBsAg Seropositivity among rural population attending inpatients and outpatients at tertiary care center with special consideration to childbearing age women.Material & Method: This retrospective study was conducted in the Department of Microbiology for three months in a tertiary care center catering rural population. A total of 1463 patients attending outdoor and indoor, were screened for HBsAg by lateral flow based rapid immunochromatographic card test (ICT) manufactured by J Mitra & Co Pvt Ltd.Results: Seropositivity of HBsAg was 41/1463(2.80%). Seropositivity was seen more in males 27/756(3.57%) as compared to females 14/707(1.98%). Age range 31-45 years was found to have highest prevalence rate with seropositivity of 15/279(5.38%). Among patients screened for HbsAg, we observed seropositivity of 2.37% (12/505) among women of childbearing age with age range 16 to 45 years.Conclusion: Findings in this study significantly contribute to the understanding of actual epidemiology of HBsAg in rural population especially women of childbearing age. Therefore, we should make efforts to prevent HBV infection by focusing on associated risk factors.